Prevalence and Control of Diabetes in Chinese Adults - Xu, Yu; Wang, Limin; He, Jiang; Bi, Yufang; Li, Mian; Wang, Tiange; Wang, Linhong; Jiang, Yong; Dai, Meng; Lu, Jieli; Xu, Min; Li, Yichong; et al. (JAMA : the journal of the American Medical Association, 2013)
IMPORTANCE Noncommunicable chronic diseases have become the leading causes of mortality and disease burden worldwide. OBJECTIVE To investigate the prevalence of diabetes and glycemic control in the Chinese adult population. DESIGN, SETTING, AND PARTICIPANTS Using a complex, multistage, probability sampling design, we conducted a cross-sectional survey in a nationally representative sample of 98 658 Chinese adults in 2010. MAIN OUTCOMES AND MEASURES Plasma glucose and hemoglobin A1c levels were measured after at least a 10-hour overnight fast among all study participants, and a 2-hour oral glucose tolerance test was conducted among participants without a self-reported history of diagnosed diabetes. Diabetes and prediabetes were defined according to the 2010 American Diabetes Association criteria; whereas, a hemoglobin A1c level of <7.0% was considered adequate glycemic control. RESULTS The overall prevalence of diabetes was estimated to be 11.6% (95% CI, 11.3%-11.8%) in the Chinese adult population. The prevalence among men was 12.1% (95% CI, 11.7%-12.5%) and among women was 11.0% (95% CI, 10.7%-11.4%). The prevalence of previously diagnosed diabetes was estimated to be 3.5% (95% CI, 3.4%-3.6%) in the Chinese population: 3.6% (95% CI, 3.4%-3.8%) in men and 3.4% (95% CI, 3.2%-3.5%) in women. The prevalence of undiagnosed diabetes was 8.1% (95% CI, 7.9%-8.3%) in the Chinese population: 8.5% (95% CI, 8.2%-8.8%) in men and 7.7% (95% CI, 7.4%-8.0%) in women. In addition, the prevalence of prediabetes was estimated to be 50.1% (95% CI, 49.7%-50.6%) in Chinese adults: 52.1% (95% CI, 51.5%-52.7%) in men and 48.1% (95% CI, 47.6%-48.7%) in women. The prevalence of diabetes was higher in older age groups, in urban residents, and in persons living in economically developed regions. Among patients with diabetes, only 25.8% (95% CI, 24.9%-26.8%) received treatment for diabetes, and only 39.7% (95% CI, 37.6%-41.8%) of those treated had adequate glycemic control. CONCLUSIONS AND RELEVANCE The estimated prevalence of diabetes among a representative sample of Chinese adults was 11.6% and the prevalence of prediabetes was 50.1%. Projections based on sample weighting suggest this may represent up to 113.9 million Chinese adults with diabetes and 493.4 million with prediabetes. These findings indicate the importance of diabetes as a public health problem in China.